Comparative study of the fat body in some genera of the attini tribe (Hymenoptera: Formicidae) - Roma, Gislaine Cristina; Bueno, Odair Corrêa; Mathias, Maria Izabel Camargo [UNESP] (My University, 2005)
The Cyphomyrmex rimosus Spinola and Mycetarotes parallelus Emery species of ants, considered basal, and Acromyrmex disciger Mayr and Atta laevigata Smith, considered derived, have fat bodies specially distributed on their gaster, around their organs and right below the cuticle. The fat body is formed by trophocytes, which are characterized by their pronounced vacuolization of the cytoplasm and the irregular morphology of their nuclei caused by the pressure exerted by cytoplasmic vacuoles. In C. rimosus, the nuclei are more regular, presenting an oval or a star form. In A. disciger and A. laevigata the nuclei present chromatin in a cord form, while in C. rimosus and M. paralellus the chromatin is uniformly distributed in the nucleoplasm, very condensed in the latter species. The parietal trophocytes of A. disciger show cytoplasm with a smaller quantity and smaller sizes of vacuoles compared to ones from the perivisceral region, the opposite is observed in C. rimosus. In A. laevigata and M. parallelus there were no differences observed in their cytoplasm between both regions of cells. In the trophocytes of C. rimosus, A. disciger, A. laevigata, there was a reticular aspect of the cytoplasm observed in the region between vacuoles, not seen on M. parallelus. Another cellular type, oenocyte, was found associated with the fat body cells, and is dispersed between trophocytes with an inner contact to them, but no membrane fusion with them. The oenocytes have a spherical form and are smaller than the trophocytes; they have acidophilic cytoplasm with a small quantity of small vacuoles, and round nuclei.
Keywords: Acromyrmex disciger; Ants; Atta laevigata; Cyphomyrmex rimosus; Fat body; Mycetarotes parallelus; Attini; Formicidae; Hymenoptera